Impact of Depression, Resilience, and Locus of Control on Adjustment of Health-Related Expectations in Aging Individuals With Chronic Illness - Schönenberg, Aline; Zipprich, Hannah M.; Teschner, Ulrike; Prell, Tino (Frontiers in Psychology, 2022)
Objectives: Quality of Life (QoL) depends on the discrepancy between desired and current experiences (referred to as the Calman gap), thus in chronic illness, adjustment of expectations and interpretation of the current situation are crucial. Depression is known to influence this gap, and the present study aims to further assess the role of resilience and health locus of control (HLC). Methods: 94 patients (age M = 71.8, SD = 7.7 years) with neurological disorders were screened via telephone regarding depression, resilience and HLC. Current and desired state of several life domains were assessed, such as Fitness, General Health, Pain, Daily Activities, Finances, Leisure and Family. Elastic net regularization and analyses of variance were used to disentangle the impact of depression, resilience, HLC, and sociodemographic factors on the perception of current and desired state, and the gap between both. Results: A gap was present for all domains but largest for pain. Interpretation of the current state was linked to desired state, HLC, and age. All gaps were related to depression; certain domains were in addition influenced by resilience, HLC and sociodemographic factors. Of note, for most domains, patients did not select the highest possible desired state. Conclusion: Older patients with neurological disorders report a gap between current and desired state for many aspects of life. Adjusting expectations is beneficial in the face of declining health, but a reasonably increased desired state may positively influence the perception of the current situation. Depression negatively influences the interpretation of the Calman gap.